2021
DOI: 10.1182/blood.2020007263
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of plasminogen and a novel plasminogen receptor, Plg-RKT, on activated human and murine platelets

Abstract: Plasminogen activation rates are enhanced by cell surface binding. We have previously demonstrated that exogenous plasminogen binds to phosphatidylserine-exposing and spread platelets. Platelets contain plasminogen in their α-granules but secretion of plasminogen from platelets has not been studied. Recently, a novel transmembrane lysine-dependent plasminogen receptor, Plg-RKT, has been described on macrophages. Here, we analyzed the pool of plasminogen in platelets and examined whether platelets express Plg-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Plg-R KT is considered to play various pathophysiological roles in vivo , and conventionally developed Plgrkt −/− mice were utilized to prove its roles in inflammatory macrophage recruitment (Miles et al ., 2017), cutaneous wound healing (Ny et al ., 2020), platelet activation (Whyte et al ., 2021) and adipose tissue development (Samad et al ., 2021). It has been considered that Pg activation in the mammary grand tissues is essential for normal lactation due to the phenotypes manifested by conventional Plg −/− (Ploplis et al ., 1995) and Plgrkt −/− (Miles et al ., 2018) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Plg-R KT is considered to play various pathophysiological roles in vivo , and conventionally developed Plgrkt −/− mice were utilized to prove its roles in inflammatory macrophage recruitment (Miles et al ., 2017), cutaneous wound healing (Ny et al ., 2020), platelet activation (Whyte et al ., 2021) and adipose tissue development (Samad et al ., 2021). It has been considered that Pg activation in the mammary grand tissues is essential for normal lactation due to the phenotypes manifested by conventional Plg −/− (Ploplis et al ., 1995) and Plgrkt −/− (Miles et al ., 2018) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Plg-R KT demonstrates affinity for tPA and is known to co-localize with uPAR on monocytes and macrophages ( 92 ). We have subsequently identified Plg-R KT on platelets and found that it is directly responsible for anchoring plasminogen to the activated platelet membrane ( 93 ). Interestingly, while platelets do not express uPAR, we have shown that the platelet membrane stimulates reciprocal activation of scuPA and plasminogen to their active forms ( 94 ), thereby highlighting the importance of cellular surfaces in regulating profibrinolytic activity.…”
Section: Localization Of Fibrinolytic Activitymentioning
confidence: 99%
“…More recently, Whyte et al demonstrated the presence of Plg-R kt on the platelet surface. Genetic ablation of Plg-R kt reduces plasminogen binding by roughly 50%, suggesting the central role of this receptor in the retention of plasminogen on the activated platelets [ 47 ].…”
Section: Molecular Connections Between Platelets and Components Of Pl...mentioning
confidence: 99%